POSSIBILITIES OF APPLICATION OF IMMUNOLOGICAL TESTS IN THE DIFFERENTIAL DIAGNOSIS OF PULMONARY TUBERCULOSIS IN CHILDREN WITH NONSPECIFIC CHRONIC BRONCHOLOGICAL PATHOLOGY - Yu. E. Ovchinnikova; N. V. Korneva; P. V. Gavrilov (Журнал инфектологии, 2016)
The introduction of new immunological tests (test with Diaskintest) enables timely, but refer the child for examination in phthisiopulmonology the presence of comorbidity. A clinical case of combined pathology of the lungs  of a 13-year-old child with a polo-positive result with samples Diaskintest, the presence of clinical  symptoms and  radiographic changes in the lungs.  The patient entered the clinic of the Institute after five  years  of observation and  treatment failures  pulmonologist with suspected tuberculosis after five years of the lower lobe of the left lung in the phase  of destruction and contamination to examination in order to clarify the diagnosis and a course  of specific therapy. A child  with  concurrent chronic bronchopulmonary pathology was  diagnosed lung  TB. The need for a detailed and  comprehensive study of the  history of the disease, the use of a complex of modern methods of inspection and timely solution of millet  Prompt intervention is determined in a subsequent treatment efficacy, minimal residual  changes and restore the functional state  of the child’s body.